Optimization, characterization, and DFT study of activated-biochar from lignocellulosic biomass for fluoroquinolone antibiotic adsorption - Kawtar Ezzahi; Imad Rabichi; Hasna Befenzi; Eric Record; Taoufiq Bouzid; Abdelghani Yaacoubi; Abdelaziz Baçaoui; Youssef Habibi; Loubna El Fels (Results in Engineering)
The presence of fluoroquinolone antibiotics in water bodies poses a significant environmental concern due to their persistence and potential ecological risks. This study explores the adsorption efficiency of BC and AC derived from lignocellulosic biomass for the removal of ciprofloxacin (CIP), levofloxacin (LEV), and enrofloxacin (ENR) from aqueous solutions. The results revealed that KOH activation significantly enhanced the surface area of AC (829.76 m²/g), compared to BC (258.72 m²/g), leading to a higher adsorption capacity. Adsorption kinetics were most accurately represented by the pseudo-second-order model, indicating that chemisorption is the primary mechanism in the adsorption process. Equilibrium data were fitted to both the Langmuir and Freundlich isotherm models, with the Langmuir model yielding the best fit, confirming monolayer adsorption. The maximum adsorption capacities (qm) obtained for AC were 147.68 mg/g for CIP, 134.29 mg/g for LEV, and 128.53 mg/g for ENR, highlighting the superior adsorption potential of AC compared to BC. Thermodynamic research found that the adsorption process was spontaneous and endothermic, with rising temperature favoring adsorption. Furthermore, the Elovich model provided additional insights into the heterogeneous nature of the adsorption sites and the strong affinity between the antibiotics and the adsorbent surface. The results demonstrate the high efficiency of AC in removing pharmaceutical pollutants, emphasizing its potential for application in wastewater treatment and environmental remediation.